Kemampuan Berpikir Aljabar Siswa Climber dalam Menyelesaikan Masalah SPLDV - Istikomah Istikomah; Erni Puji Astuti; Heru Kurniawan (Department of Mathematics Education, Universitas Muhammadiyah Purwokerto, Indonesia, 2020)
The aim of this study is to analyze the algebraic thinking ability of students in SPLDV problems solving. This research was conducted by students in eighth grade with AQ climber type. The type of this study is qualitative research with a phenomenological approach. The technique of taking the subject is a purposive technique with two students as the subject that chosen with the AQ climber category. The instruments that used in this research are SPLDV matter solving sheets, interview guidelines, and field notes. The techniques of collecting data are tests, interviews, and field notes. The steps in analyzing data are data reduction, data presentation, and drawing conclusions. The results showed that climber students are able to think algebraic views from their activities, namely generational activity, transformational activity, and global meta-level activity. The indicators achieved in generational activities are students can understand the equations that contain variables namely the meaning of the equal sign and also students are able to understand the solution of equation. The indicators achieved in transformational activities are students being able to say terms, expand, substitute, solve equations, simplify expressions, and be able to change equations into equivalent equations. Whereas in global meta-level activities students are able to use algebra to predict a problem in mathematics and be able to model mathematics that related to algebra.